Transcriptomic and proteomic profiling of human diabetic heart disease. (3rd October 2022) - Gollmer, J; Potter, L; Vosko, I; Tomin, T; Birner-Gruenberger, R; Von Lewinski, D; Sedej, S; Scherr, D; Wende, A R; Rainer, P; Zirlik, A; Bugger, H
Abstract: : Studies in animal models demonstrated the capability of type 2 diabetes (T2D) to induce cardiac dysfunction in the absence of vascular disease. However, whether and how T2D also impairs structure and function in human hearts remains poorly understood. Here, we performed transcriptional and proteomic profiling of left ventricular samples of 8 subjects with T2D, preserved EF (63, 5%) and no history of ischemic heart disease (= diabetic cardiomyopathy; DbCM), 7 subjects with T2D, reduced EF (26, 9%) and ischemic heart disease (= diabetic heart failure; DbHF), and 15 non-diabetic individuals with normal EF (64, 7%) serving as controls. Among 1168 proteins identified by LC-MS/MS, 146 proteins were differentially regulated in DbHF, but only 66 in DbCM. Pathway analysis revealed downregulation of energy metabolic proteins, but upregulation of proteins involved in oxidative stress and inflammatory response. In DbCM, pathways of structural remodeling, cardiomyocyte proliferation, and mechanotransduction were upregulated. Bulk RNA sequencing revealed 1795 differentially regulated genes in DbHF, and 527 in DbCM, with only 128 genes being commonly regulated. DbHF, but not DbCM, could be clearly discriminated from controls by hierarchical clustering. While inflammation/immunity were major regulated pathways in DbHF, extracellular matrix remodeling and cellular growth were the most regulated pathways in DbCM. Thus, the differential regulation of biological pathways in DbCM versus DbHF suggests the existence of two distinct disease entities rather than DbHF being an advanced disease stage of DbCM. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Austrian Diabetes Society